Life Skills of Adolescents in a Catholic University in Central Philippines - Vergara, Trisha Marie; Tajonera, Chris Feli Joy (Technium Social Sciences Journal, 2023)
The 21st Century skills introduced diverse skills called life skills to go through the basics to navigate and deal with everyday demands of life. This study aimed to assess the life skills of adolescents in a Catholic University in Central Philippines in terms of self-awareness, effective communication, empathy, interpersonal relations, creative and critical thinking, decision-making, problem-solving, coping with emotions, and coping with stress. Similarly, it determined the relationship between the demographics and life skills. Using a quantitative design, a 100-item standardized questionnaire was responded by 268 adolescents enrolled in academic year 2022-2023. Generally, their level of life skills was rated average, which indicates that they have tendencies to regress depending on the severity of the situations or may progress further when they feel they have enough resources to respond in changes or difficulties of life. The lowest area was coping with stress and the highest area was self-awareness. Meanwhile, their sex, birth order, and family structure were found no relationship with life skills. Meaning, there might be other factors that may influence the life skills and may serve as directions for future researchers. Hence, continuous enhancement is essential to help the adolescents to reach their optimum level and maintain their life skills to deal with the life’s challenges and demands.